EVALUATION OF EFFLEURAGE MASSAGE WITH OLIVE OIL ON THE DEGREE OF DECUBITUS IN BEDREST PATIENTS - Angelina Purwanjani; Theresia Tatik Pujiastuti; Tandean Arif Wibowo (Jurnal Keperawatan Sriwijaya, 2026)
Aim: This study aims to evaluate the effects of effleurage massage with olive oil on the severity of pressure ulcers in bedridden patients at a private hospital in Yogyakarta. Methods: This study used a quasi-experimental design with a pretest-posttest control group approach. A total of 30 participants were selected using accidental sampling and divided into two groups: the intervention group (n = 15), which received effleurage massage with olive oil twice daily for three days, and the control group (n = 15), which did not receive the intervention. The degree of pressure ulcers was assessed through clinical observation based on the pressure ulcer staging classification (Braden Score). Data analysis was performed using the Wilcoxon signed-rank test to analyze changes in the degree of pressure ulcers before and after the intervention in each group, while differences in the degree of pressure ulcers between groups after the intervention were analyzed using the Mann–Whitney U test. Results: Most respondents were aged ≥60 years (90%), male (66.7%), and had a Braden score in the very high-risk category (76.7%). In the intervention group, 86.7% of respondents did not develop pressure ulcers and 13.3% developed Stage I pressure ulcers, whereas in the control group, 73.3% did not develop pressure ulcers, 20.0% developed Stage I pressure ulcers, and 6.7% developed Stage II pressure ulcers. The results of the Wilcoxon test showed no significant change in pressure ulcer stage in either the intervention group (p=1.000) or the control group (p=0.157). The results of the Mann–Whitney test showed no difference in post-test pressure ulcer stage between the intervention and control groups (p=0.512). Conclusion: The administration of effleurage massage using olive oil did not have a significant effect on the severity of pressure ulcers in bedridden patients at a private hospital in Yogyakarta. Future studies are recommended to use a larger sample size, a longer intervention duration and observation period, and a study design that allows for the evaluation of changes in condition before and after the intervention.